An Evaluation of a Technology Enhanced Learning Tool (Labtutor) From the Perspective of Undergraduate Student Nurses - McMullan, Johanna (International Journal of Innovative Research in Medical Science, 2017)
The efficiency of large group teaching (lectures) has long been called into question with much research high lighting low levels of student participation, and poor attention spans leading to a lack of engagement with learning which inhibits deep learning. Small group teaching and Enquiry Based Learning (EBL) are methods of teaching that can help promote deep learning. There is also a growing need and demand for Technology Enhanced Learning to suit changing lifestyles. The Labtutor® System, is one such piece of software that is designed to incorporate EBL and small group teaching quality into the large group setting. This study provides a descriptive survey of adult nursing student’s perceptions of the Labtutor system following its use in two Life Science modules within an undergraduate nursing programme. A convenience sample of first year adult nursing students (n= 115) were identified to complete a 32 item questionnaire (appendix three). Participants reported overall that they enjoyed using the system and found it beneficial to their learning specifically: Increased engagement with material in online learning as a result of using the system. Increased participation and levels of interactivity in the lecture as a result of using the system. Increased enhancement of learning as a result of using the system and Usefulness of the formative assessment facilitated by using the system. The study concludes that Labtutor® system and other such methods of Technology Enhanced Learning packages if used correctly can enhance learning.